Effectiveness of a parenting programme to reduce violence in a cash transfer system in the Philippines: RCT with follow-up - Lachman, J; Alampay, LP; Jocson, RM; Alinea, C; Madrid, B; Ward, C; Hutchings, J; Mamauag, BL; Garilao, MAVFV; Gardner, F (Elsevier, 2021)
Background